2020
DOI: 10.1177/0255761419898313
|View full text |Cite
|
Sign up to set email alerts
|

Peer tutoring for improvement in rhythm reading fluency and comprehension

Abstract: Peer tutoring in music education is an under-researched but burgeoning area of study. This study aims to assess the effects of the same-age peer tutoring project Ritmos en dos on rhythm reading fluency and comprehension. For this purpose, 24 students from the third grade of secondary education participated in the project. This research utilises a mixed-methods sequential explanatory design, combining (a) a pretest-posttest control group design, with (b) a qualitative study to understand the possible quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…Through the study of a highly structured fixed peer tutoring project for rhythm reading fluency, Duran et al (2020) concluded that this was a valid tool for the improvement of pulsation, rhythmic precision, analysis and meta-cognitive reflection. However, the scores obtained in comprehension suggested a limitation in the type of help provided in this aspect, decreasing the opportunities of the tutors when reflecting on and building their own learning.…”
Section: Results: Approaches Of Peer Tutoring In Music Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the study of a highly structured fixed peer tutoring project for rhythm reading fluency, Duran et al (2020) concluded that this was a valid tool for the improvement of pulsation, rhythmic precision, analysis and meta-cognitive reflection. However, the scores obtained in comprehension suggested a limitation in the type of help provided in this aspect, decreasing the opportunities of the tutors when reflecting on and building their own learning.…”
Section: Results: Approaches Of Peer Tutoring In Music Educationmentioning
confidence: 99%
“…Therefore, this tool becomes a meaningful learning experience (e.g. Darrow, 2005;Duran et al, 2020;Goodrich, 2007;Johnson, 2015). This structure would encourage students to know their role and function, allowing more flexibility over time.…”
Section: Discussionmentioning
confidence: 99%
“…They were also told that they all shared a common goal in this process: ensuring that every classmate understood and finished the exercises and problems by the end of each tutoring session. "Pause, Prompt, and Praise" techniques were also discussed, and the importance of patience and respect was emphasized (Duran et al, 2020). Moreover, students were told that interactions between them had to be rich in mathematical content, so they should not talk about other non-related issues during the PT sessions.…”
Section: Student Trainingmentioning
confidence: 99%
“…They were also told that they all shared a common goal in this process: ensuring that every classmate understood and finished the exercises and problems by the end of each tutoring session and knew how to use the math digital tools. "Pause, Prompt, and Praise" techniques were also discussed, and the importance of patience and respect was emphasized [39]. Moreover, students were told that interactions between them had to be rich in mathematical content, so they should not talk about non-related issues during the peer tutoring sessions.…”
Section: Student Trainingmentioning
confidence: 99%